Evaluation of particle size distribution of granular blasting materials based on the fractal theory. (October 2019) - Ji, Jiejie; Yao, Qiang; Wu, Faming; Li, Hongtao
The particle size distribution of granular blasting materials has a vital influence on the filling quality of earth-rockfill dams. The engineering experience-based method used to evaluate the particle size distribution has shortcomings at both the theoretical and practical aspects. This article proposes a new evaluation method based on the fractal theory. Grading sieve tests on granular materials, mass fractal analysis of particle size distribution, and a probability distribution model test of the characteristic parameters are used to revise the functional relationships between the fractal dimension D and the uniformity coefficient/curvature coefficient ( Cu / Cc ) of the grading curve. The feasibility of using D to evaluate the particle size distribution and the optimal fine grain content is then analyzed and determined. According to the results, the geometric shapes of the granular blasting materials have fractal characteristics, and their particle size distribution has a fractal distribution. The ranges of D where the rockfill and transition materials have a good particle size distribution are D  = 2.254–2.529 and D  = 2.358–2.559, corresponding to optimal fine grain content of 1.953%–11.805% and 10.268%–23.123%, respectively. Fractal dimension has a solid theoretical basis and strong practical applicability as an evaluation index for the particle size distribution of granular blasting materials.